Land Evaluation of Recreation and Ecotourism Services Using Multi-Criteria Evaluation Process: A Case Study of Aswan City, Egypt - Valánszki, István; Abualhagag, Asmaa (Journal of Environmental Geography, 2022)
Land suitability of Recreation and Ecotourism (RE) is the process of predicting the potential use of land on the basis of its attributes. Decisions on land use have always been part of the evolution of human society. The integration of this GIS using the multicriteria decision analysis approach provides an environment to the decision-makers in citing areas using land suitability analysis procedures. The present study aims at evaluating the land use suitability for Recreation and Ecotourism development in the rural–urban in Aswan city-Egypt. This is achieved by using the GIS-based Multi Criteria Decision Analysis (GIS-MCDA) on twelve various economic, environmental and urban criteria This study was carried out within the framework of an Analytic Hierarchy Process (AHP) as a multi-criteria evaluation approach by integrating it with the Geographic Information System (GIS). Hence, based on the analysis and findings made in this research, finding suitable locations using the land suitability model for future recreation and ecotourism development is highly helpful. Results can be useful in the planning of public facilities and future land use planning in Aswan city.